Covid-19 Knowledge and Perceptions Among Dental Specialists: A Cross-Sectional Online Questionnaire Survey - Aldhuwayhi S; Mallineni SK; Sakhamuri S; Thakare AA; Mallineni S; Sajja R; Sethi M; Nettam V; Mohammad AM (Dove Medical Press, 2021)
Sami Aldhuwayhi,1 Sreekanth Kumar Mallineni,2- 4 Srinivasulu Sakhamuri,5 Amar Ashok Thakare,1 Sahana Mallineni,6 Rishitha Sajja,7 Mallika Sethi,8 Venkatesh Nettam,9 Azher Mohiuddin Mohammad10 1Department Prosthodontics, College of Dentistry, Majmaah University, Al-majmaah, 11952, Saudi Arabia; 2Department of Preventive Dental Sciences, College of Dentistry, Majmaah University, Al-majmaah, 11952, Saudi Arabia; 3Department of Pediatric and Preventive Dentistry, Narayana Dental College and Hospital, Nellore, Andhra Pradesh, India; 4Department of Pediatric and Preventive Dentistry, Saveetha Dental College and Hospitals, Saveetha Institute of Medical and Technical Sciences, Chennai, Tamil Nadu, India; 5Department of Conservative Dentistry & Endodontics, Narayana Dental College and Hospital,, Nellore, Andhra Pradesh, India; 6Department of Periodontology, Krishna Institute of Medical Sciences, Nellore, AP, India; 7Data Manager, Bristol Myers Squibb, New Brunswick, NJ, USA; 8Department of Periodontology, ITS Dental College, Muradnagar, Ghaziabad, Uttar Pradesh, India; 9Department of Orthodontics, Narayana Dental College and Hospital, Nellore, Andhra Pradesh, India; 10Oral Maxillofacial Surgery, Military Hospital, Riyadh, Saudi ArabiaCorrespondence: Sreekanth Kumar MallineniPediatric Dentistry, Department of Preventive Dental Science, College of Dentistry, Majmaah University, AlMajmaah, 11952, Saudi ArabiaTel +966-507780161Email s.mallineni@mu.edu.saBackground: The recent outbreak of coronavirus (COVID-19) caused a significant impact on dentistry. It is imperative to have sufficient knowledge of COVID-19 to manage patients in the dental operatory.Aim: To assess the knowledge and perceptions of dentists from different specialities about COVID-19 disease.Settings and Design: Cross-sectional online survey.Materials and Methods: This study used a descriptive cross-sectional study design with a self-administered questionnaire. The questionnaire included three sets of 23 questions [Demographic-4; Source of information-1; Knowledge-10 and Perceptions-8]. The comparison of mean scores of knowledge and perceptions were interpreted based on the occupation of dental specialists.Statistical Analysis Used: The association between demographic variables and dental specialists' knowledge and perception scores was carried out using SPSS (Version IBM 21.0, NY, USA).Results: A total of 429 dentists from various specialties participated in the present study. The study had obtained a overall good knowledge score (92.7%) with a mean value of 8.86 + 0.22, and a perception score (70.7%) with a mean value of 5.4+0.3. The present study reports a statistically significant difference between age (p=0.03) and knowledge source (p< 0.05). The multi variate regression analysis showed that dentists' specialty had no significant effect on knowledge and perception.Conclusion: The study reports sufficient knowledge and perception scores. Oral maxillofacial surgeons showed higher knowledge scores, while prosthodontics and periodontics achieved good mean scores for perception on COVID-19. Social media and health authorities played an equally important role in the overall knowledge of the source of information related to COVID-19.Keywords: COVID-19, dentists, infection, questionnaire, dentistry